Late-Holocene climate and ecosystem history from Chesapeake Bay sediment cores, USA - Willard, D. A.; Cronin, T. M.; Verardo, S. (Holocene, 2003)
Palaeoclimate records from late-Holocene sediments in Chesapeake Bay, the largest estuary in the USA, provide evidence that both decadal to centennial climate variability and European colonization had severe impacts on the watershed and estuary. Using pollen and dinoflagellate cysts as proxies for mid-Atlantic regional precipitation, estuarine salinity and dissolved oxygen (DO) during the last 2300 years, we identified four dry intervals, centred on AD 50 (P1/D1), AD 1000 (P2/D2), AD 1400 (P3) and AD 1600 (P4). Two centennial-scale events, P1/D1 and P2/D2, altered forest composition and led to increased salinity and DO levels in the estuary. Intervals P3 and P4 lasted several decades, leading to decreased production of pine pollen. Periods of dry mid-Atlantic climate correspond to 'megadroughts' identified from tree-ring records in the southeastern and central USA. The observed mid-Atlantic climate variability may be explained by changes in atmospheric circulation resulting in longer-term, perhaps amplified, intervals of meridional flow. After European colonization in the early seventeenth century, forest clearance for agriculture, timber and urbanization altered estuarine water quality, with dinoflagellate assemblages indicating reduced DO and increased turbidity.
650thTimes Cited:56Cited References Count:101